Near–infrared photodynamic inactivation of S. pneumoniae and its interaction with RAW 264.7 macrophages - Leite, Ilaiáli S.; Geralde, Mariana C.; Salina, Ana C.G. [UNESP]; Medeiros, Alexandra I. [UNESP]; Dovigo, Lívia N. [UNESP]; Bagnato, Vanderlei S.; Inada, Natalia M. (Wiley, 2018)
Pneumonia is the main cause of children mortality worldwide, and its major treatment obstacle stems from the microorganisms increasing development of resistance to several antibiotics. Photodynamic therapy has been presenting, for the last decades, promising results for some subtypes of cancer and infections. In this work we aimed to develop a safe and efficient in vitro protocol for photodynamic inactivation of Streptococcus pneumoniae, one of the most commonly found bacteria in pneumonia cases, using two near-infrared light sources and indocyanine green, a FDA approved dye. Photodynamic inactivation experiments with bacteria alone allowed to determine the best parameters for microbial inactivation. Cytotoxicity assays with RAW 264.7 macrophages evaluated the safety of the PDI. To determine if the photodynamic inactivation had a positive or negative effect on the natural killing action of macrophages, we selected and tested fewer indocyanine green concentrations and 10 J/cm2 on macrophage-S. pneumoniae co-cultures. We concluded that ICG has potential as a photosensitizer for near-infrared photodynamic inactivation of S. pneumoniae, producing minimum negative impact on RAW 264.7 macrophages and having a positive interaction with the immune cell's microbicidal action. (Figure presented.).
Keywords: antimicrobial photodynamic therapy; indocyanine green; macrophage; photodynamic inactivation; Streptococcus pneumoniae